FIRST RECORD OF AULACIDAE (HYMENOPTERA, EVANIOIDEA) FROM URUGUAY WITH DESCRIPTION OF A NEW SPECIES OF Aulacus (Boletín de la Sociedad Zoológica del Uruguay, 2020)
The presence of the parasitoid wasp family Aulacidae (Hymenoptera, Evanioidea) in Uruguay is documented for the first time. Two species are recorded, Aulacus castiglionii Perioto, Lara, Turrisi, sp. nov., and Pristaulacus ambiguus (Schetterer, 1890).